Fabrication of Large‐Area Uniform Nanometer‐Thick Functional Layers and Their Stacks for Flexible Quantum Dot Light‐Emitting Diodes. Issue 2 (9th December 2021) - Zhang, Weimin; Du, Jinhong; Wei, Qinwei; Zhang, Dingdong; Pei, Songfeng; Tong, Bo; Liu, Zhibo; Liang, Yan; Cheng, Hui‐Ming; Ren, Wencai
Abstract: Large‐area fabrication and stacking of various nanometer‐thick functional layers from solutions is essentially important for the construction of flexible thin‐film optoelectronic devices, but very challenging. The existing fabrication methods suffer from either non‐uniformity caused by the coffee‐ring effect or serious solution waste (excess of 90% for spin coating), and are hard to scale up and create stacks. Here, it is shown that centrifugal casting is a universal, scalable, and efficient method to fabricate uniform nanometer‐thick films and their stacks of various materials. The coffee‐ring effect is effectively suppressed, the solution utilization ratio is higher than ≈61%, and the films/stacks show a smooth surface/high‐quality interface. Using this method, flexible quantum dot light‐emitting diode displays with uniform luminance in a large lighting area of ≈115 cm 2 that have not been achieved even on rigid substrates by the existing methods, are realized. This efficient and low‐cost solution processing method paves a way for large‐area fabrication of various flexible thin‐film optoelectronic devices. Abstract : A universal, scalable, and efficient centrifugal casting method is developed to fabricate uniform nanometer‐thick films and their stacks of various materials. The coffee‐ring effect is effectively suppressed, and the films/stacks show a smooth surface/high‐quality interface. Flexible quantum dot light‐emitting diode displays with uniform luminance in a large lighting area of ≈115 cm 2 are demonstrated.